Mussel adhesive proteins as surgical sealants in post-extraction: Literature review: Mussel adhesive proteins sebagai surgical sealant pada pasca pencabutan gigi: Kajian pustaka - Haswamati Hasan; Ramadhan Alfitrah Syamsir Dewang (Makassar Dental Journal, 2022)
Background and objective: Tooth extraction is a dental procedure of removing a tooth from its socket, causing an injury. Dental socket wounds that are directlyexposed to the oral environment allow the entry of pathogenic micro-organisms that can cause post-extraction bleeding, alveolar osteitis, oroantral fistula, and others. Recent studies have shown that the use of mussel adhe-sive proteins (MAPs) without sutures or staples can accelerate socket wound closure or stopbleeding after tooth extraction. Con-clusion: MAPs that have been synthesized into injectable citrate-based mussel-inspired bioadhesive have the potential assurgical sealants after tooth extraction because they have strong adhesive properties in wet environments, good esthetics, atraumatic, and short operating time.